Effect of Herringbone Technique on the Students’ Achievement in Reading Narrative Text at SMA Swasta Budisatrya in Academic Years of 2021/2022 - Dinda Suryani; Rini Fadhilah (Medan Resource Center, 2023)
The objective of this research is finding out whether or not there is significant The Effect of Using Herringbone Technique on Students’ Achievemenet in Reading Narrative Text at the second semester of the grade of SMAS Budisatrya Medan in academic year 2021/2022.Reading comprehension is the ability to get comprehension, including to recognize the unfamiliar words or sentence in the text. Comic series is one of media that uses some comics related to the story given. These comics has function to describe the story. It is an appropriate media to be taught in Senior High School level to open up their mind widely by reading passage.There were two variables in this research. The independent variable is the word herringbone technique (X) and dependent variable is the students’ reading comprehension (Y). The research methodology in this research is Quasi experimental design with experimental and control class. The population of this research is the eight grade of SMAS Budisatrya Medan. In determining the sampling technique. The samples of research were 2 classes VIII A consisted of 15 students while in VIII B consisted 15 students. In collecting the data, there were pre-test and post-test and instrument. After giving the post-test ,the researcher analyzed the data of research . From the result, it was obtained that t-count is higher than t-critical (46 >39,33). Therefore, there is significant influence of using series pictures towards students’ reading comprehension in narrative text at the second semester of the eleven grade of SMAS Budisatrya Medan in academic year 2021/2-2022.